2017
DOI: 10.1080/09674845.2017.1278884
|View full text |Cite
|
Sign up to set email alerts
|

Integron occurrence is linked to reduced biocide susceptibility in multidrug resistantPseudomonas aeruginosa

Abstract: The current study reveals the presence of different classes of integrons, with class I being predominant. Class I integron may be responsible for generating MDR P. aeruginosa isolates with reduced susceptibility to biocides. This linkage between integrons and biocide resistance in MDR-Pseudomonas isolates is notable and could be clinically important. Strict antibiotic prescription policies and the adequate use of biocides could help in controlling this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
1
18
2
Order By: Relevance
“…MDR isolates represents a prominent health problem in Egypt due to several factors including misuse of antibiotics and biocides 30 . In the current study, 50 P. aeruginosa isolates were recovered from urine samples, all the isolates were MDR (100%), this MDR rate was higher than rates reported previously in Egypt which ranged from 34% – 56% 31 33 ; this may reflect higher resistance rate in case of urinary tract infections. Other global studies showed even lower MDR rates; 5.9% in Canada 34 , 19% in Germany 35 , 19.6 % in Malaysia 36 and 20.7% in Nepal 37 .…”
Section: Discussioncontrasting
confidence: 58%
“…MDR isolates represents a prominent health problem in Egypt due to several factors including misuse of antibiotics and biocides 30 . In the current study, 50 P. aeruginosa isolates were recovered from urine samples, all the isolates were MDR (100%), this MDR rate was higher than rates reported previously in Egypt which ranged from 34% – 56% 31 33 ; this may reflect higher resistance rate in case of urinary tract infections. Other global studies showed even lower MDR rates; 5.9% in Canada 34 , 19% in Germany 35 , 19.6 % in Malaysia 36 and 20.7% in Nepal 37 .…”
Section: Discussioncontrasting
confidence: 58%
“…25,26 However, our results about the frequency of class 1 integrons among MDR P. aeruginosa isolates (63.4%) were comparable with a similar study carried out in Egypt (61.1%). 27 This difference may be due to the different policies and management of antibiotics for the treatment of infections in the world. Also, this rate was more varied in the southeast Asia from 38% to 95%, 3,[28][29][30][31][32] while 22% to 47% of the P. aeruginosa clinical isolates in European countries were contained the class 1 integrons between 2007 to 2013.…”
Section: Discussionmentioning
confidence: 99%
“…This, alongside the broad range of substrates (QAC compounds, disinfectants, antibiotics, etc.) that SMRs can extrude and their increasing prevalence on plasmids and integrons in clinical and multidrug-resistant strains of bacteria (13,(27)(28)(29)(30)(31)(32)(33)(34)(35), marks these proteins as important therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…The primary substrates of SMRs include quaternary ammonium compounds (QACs), a broad category that includes the fluorescent toxic molecule ethidium bromide (EtBr) and many biocides, including cetylpyridinium chloride (CPϩ), cetyltrimethylammonium bromide (CTAB), and benzalkonium chloride (BZK); the latter is a commonly used hospital disinfectant (12). Of particular relevance to the present study is the strong correlation observed between the presence of genes encoding SMR proteins in P. aeruginosa clinical isolates and increased resistance to common disinfectants, including benzalkonium chloride (13).…”
mentioning
confidence: 91%